Single-cell transcriptome analysis reveals cellular heterogeneity in mouse intra- and extra articular ligaments - Kyota Ishibashi; Kentaro Ikegami; Takashi Shimbo; Eiji Sasaki; Tomomi Kitayama; Yuzuru Nakamura; Takahiro Tsushima; Yasuyuki Ishibashi; Katsuto Tamai (Communications Biology, 2022)
Cell heterogeneity in the mouse anterior cruciate ligament (ACL) and medial collateral ligament (MCL) is demonstrated using single-cell analysis with three types of fibroblasts identified, expressing Col14a1, Col12a1, or Col22a1.